Exploring the Implementation of Safety Resilience Assessment in Industries: A Systematic Literature Review - Wirawan, Mufti; Lestari, Fatma; Djunaidi, Zulkifli; Hafia, Azka; Khaliwa, Agra Mohamad; Al Azhar, Muhammad Schehan (UI Scholars Hub, 2024)
Safety Resilience discusses how a work process can run properly not only aims at preventing adverse events, but also increasing work productivity and effectiveness by increasing resilience. The concept of resilience has been widely suggested as safety management due to its ability to support organizations to continue operating even when facing unexpected demands or scale disruptions by improving their day-to-day performance. This study used a systematic literature review to explore the implementation of safety resilience in various industries. The results showed that 50% of articles used the Resilience Assessment Grid instrument to measure safety resilience in the workplace. In brief, increased safety resilience positively improves work performance and organizational safety.